Lactate dehydrogenase: An important molecule involved in acetamizuril action against Eimeria tenella - Li-li LIU; Chen-zhong FEI; Hui DONG; Ke-yu ZHANG; Jian-jun FU; Tao LI; Fei-qun XUE (Journal of Integrative Agriculture, 2020)
Lactate dehydrogenase (LDH), a vital enzyme in anaerobic glycolysis, is closely associated with the survival of parasites. Previous studies of some parasites have shown that LDH exhibits unique physicochemical properties and molecular structures and may be an ideal potential target for diagnosis and drug screening. In this study, we aimed to investigate the effects of acetamizuril, a novel anticoccidial compound, on LDH in the second-generation merozoites of Eimeria tenella (mz-LDH). Quantitative real-time PCR, Western blot, immunofluorescence and enzyme activity assays were each applied to detect the changes of mz-LDH. Our results indicated that the mRNA and protein levels of mz-LDH were reduced upon acetamizuril treatment. Immunolocalization of mz-LDH demonstrated that considerable amount of mz-LDH was distributed around or in the nuclei of second-generation merozoites within the untreated group; in contrast, the acetamizuril-treated group had very low level of mz-LDH. Meanwhile, LDH enzyme activity assay suggested that a decreased LDH enzyme activity in both cytoplasm and nucleus of merozoites in the acetamizuril-treated group. Moreover, the induced apoptosis in second-generation merozoites by the acetamizuril was evaluated by detecting caspase 3 activity, and acetamizuril was found to significantly increase caspase 3 activity. The above findings show that LDH may play an important role in the mediating the activity of acetamizuril against coccidiosis, and further investigation into this aspect might contribute to new light on the pathogenesis of E. tenella during its interaction with acetamizuril.